PERAN INTERPOL DALAM PENEGAKAN HUKUM INTERNASIONAL TERHADAP KEJAHATAN KORPORASI GLOBAL - Yoga Deswat; Ani Purwati; Cakra Heru Santosa (Jurnal Riset Multidisiplin Edukasi, 2025)
Global corporate crime is a form of complex transnational crime that is difficult to prosecute through conventional legal means due to the involvement of multinational networks, dual jurisdictions, and non-individual perpetrators. This study aims to analyze the role of Interpol as an international legal actor in addressing global corporate crime from both functional and institutional perspectives. Using a normative juridical approach and literature review, the findings reveal that Interpol’s role remains limited by the absence of judicial authority and the diversity of legal systems among member states. Although mechanisms such as Red Notice, Operation Pangea, and the I-24/7 communication system show great potential, their effectiveness depends heavily on national responsiveness, regulatory harmonization, and political will. This study concludes that strengthening the capacity of Interpol’s National Central Bureau (NCB), reforming corporate criminal law, and enhancing international cooperation through extradition treaties and mutual legal assistance are essential to optimizing Interpol's role in combating global corporate crime effectively.